2019
DOI: 10.1016/j.htct.2018.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Test seeking: are healthcare professionals referring people to blood centers for infections marker testing?

Abstract: BackgroundTest-seeking is associated with HIV in Brazilian blood donors. This study sought to investigate the frequency with which three different donor groups: deferred donors, accepted donors who tested HIV positive [HIV (+)], and accepted donors who tested infectious disease markers negative [IDM (−)], came to the blood bank at the suggestion of a health care professional.Study design and methodsDonors deferred for reporting high-risk behaviors and participants in an HIV risk factor case-control study compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
0
5
1
Order By: Relevance
“…The reasons why HIV incidence is higher in community donors in Brazil are not known. Previous results from our group have shown that test-seeking behaviour is higher among HIV-positive blood donors than donors with no infection [15]. In our previous study, although the proportion of test seekers was higher among replacement donors, this association was not maintained in multivariable analysis [16].…”
Section: Discussioncontrasting
confidence: 54%
“…The reasons why HIV incidence is higher in community donors in Brazil are not known. Previous results from our group have shown that test-seeking behaviour is higher among HIV-positive blood donors than donors with no infection [15]. In our previous study, although the proportion of test seekers was higher among replacement donors, this association was not maintained in multivariable analysis [16].…”
Section: Discussioncontrasting
confidence: 54%
“…These findings, when added to the narrative of healthcare professionals account for a significant proportion of persons seeking tests at blood banks 6 , signal a need for further studies about this topic at earlier stages in the university environment and in the context of healthcare systems. Understanding the determinants of testseeking behavior is paramount for the maintenance of transfusion safety in Brazil.…”
mentioning
confidence: 90%
“…Alarming data about attempts to receive serological testing in blood banks at the suggestion of healthcare professionals have been reported 6 . In a recent study conducted in four large Brazilians blood banks, donors who had tested HIV positive and those previously refused for donation represented 12.6% and 11.8% of all cases, respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The main finding of the article of Moreno and collaborators 1 published in this issue of Hematology, Transfusion and Cell Therapy , is astonishing: health care professionals, mainly medical doctors, advised at-risk and HIV infected subjects to try to donate blood in order to get tested for HIV and hepatitis viruses.…”
mentioning
confidence: 99%